2020
DOI: 10.3390/ijms21228803
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Modulating Drug MP1032 with SARS-CoV-2 Antiviral Activity In Vitro: A potential Multi-Target Approach for Prevention and Early Intervention Treatment of COVID-19

Abstract: At least since March 2020, the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) pandemic and the multi-organ coronavirus disease 2019 (COVID-19) are keeping a firm grip on the world. Although most cases are mild, older patients and those with co-morbidities are at increased risk of developing a cytokine storm, characterized by a systemic inflammatory response leading to acute respiratory distress syndrome and organ failure. The present paper focuses on the small molecule MP1032, describes its … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…During this process, Tameron is oxidized, generating a photon emission that can be detected by sensitive photon-counting devices—for example, by the ultra-weak photon emission (UPE) method [ 39 ]. Tameron has been described as an antiviral agent [ 16 ], boosting the cellular antioxidant stress defenses after viral infection by activation and stabilization of the redox-sensitive NF-E2-related transcription factor 2 (Nrf2) [ 13 , 15 ], which can ameliorate the devastating impact of immune reactions on viruses, including cytokine storm [ 40 , 41 , 42 ]. Similar effects were observed for Tameron on a model of Gulf War illness—a neurological condition induced by chemical damage to brain tissue [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, Tameron is oxidized, generating a photon emission that can be detected by sensitive photon-counting devices—for example, by the ultra-weak photon emission (UPE) method [ 39 ]. Tameron has been described as an antiviral agent [ 16 ], boosting the cellular antioxidant stress defenses after viral infection by activation and stabilization of the redox-sensitive NF-E2-related transcription factor 2 (Nrf2) [ 13 , 15 ], which can ameliorate the devastating impact of immune reactions on viruses, including cytokine storm [ 40 , 41 , 42 ]. Similar effects were observed for Tameron on a model of Gulf War illness—a neurological condition induced by chemical damage to brain tissue [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its action mechanism involved the stabilization of the Nrf2 transcription factor, a known anti-inflammatory and antioxidant protein [ 15 ]. It was also tested on a mouse model and human peripheral blood mononuclear cells as an immunomodulatory agent for preventing cytokine storm, a devastating condition of the COVID-19 disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no promising treatment options are available against COVID-19 that can be recommended globally. Published studies have shown that PARP-1 inhibition limits inflammation-induced tissue damage, including acute lung injury in animal models, and PARP-1 inhibitors have therefore been discussed as a potential treatment option for COVID-19 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments demonstrated MP1032 is a drug with antiviral and immunomodulatory effects. 1 Recently, Petra Sager et al. further evaluated the efficacy and safety of MP1032 in hospitalized patients with moderate to severe COVID-19.…”
mentioning
confidence: 99%